Avaliação da qualidade ambiental em um reservatório tropical em diferentes escalas espaciais - Letícia de Morais (2013)
Reservoirs are components of the landscape that represent a distinct category of freshwater ecosystems, because they promote considerable changes in the hydrological regime and in the ecological dynamic of rivers and their watersheds. The overall goal of this work was to assess scenarios of environmental conditions in a tropical reservoir at different spatial scales, considering the land use and occupation of soil (macroscale), physical habitat characteristics (mesoscale) and limnological parameters (microscale) as predictors of conditions that potentially influence the benthic macroinvertebrate community. The estimate of taxa richness of benthic macroinvertebrates was evaluated for two types of samplers (Eckman-Birge dredge and kicking-net). This dissertation is composed of two chapters that describe the results of sampling at 40 sampling sites from a reservoir belonging the upper part of the São Francisco river basin, Minas Gerais, Brazil. Chapter 1 refers to a manuscript of disclosure, and contains the main results of this study presented in a simplified way, to be disseminated to the wider society. The chapter 2 was written as a scientific manuscript, and contains results of the applying of different spatial scales in the classification of sampling sites regarding levels of human disturbance and the influence on the benthic community in the reservoir. The results of this evaluation indicated that Três Marias reservoir is composed of sampling sites of low, medium and high disturbance on macro and mesoescales. However, the reservoir is homogeneous in microscale. The estimate of taxa richness indicated that the sampling with Eckman-Birge dredge and kicking-net exhibited similar estimates for families of benthic macroinvertebrates. There were no significant relationships between the benthic macroinvertebrate community and the division into groups in macro and mesoscale disturbances. Thus, is possible that other factors influenced the benthic community in the littoral zone of the reservoir, as the depletion in water level on the margin of the reservoir during the dry season. The results of this work highlight the need to conduct assessments of environmental quality in freshwater artificial ecosystems considering the impacts generated by its multiple uses in different patial scales.